Cognitive agents for virtual environments : first international workshop, CAVE 2012, held at AAMAS 2012, Valencia, Spain, June 4, 2012, revised selected papers - Dignum, Frank (Lecture Notes in Computer Science,, 2013)
This book constitutes the refereed post-proceedings of the First International Workshop on Cognitive Agents for Virtual Environments, CAVE 2012, held at AAMAS 2012, in Valencia, Spain, in June 2012. The 10 full papers presented were thoroughly reviewed and selected from 14 submissions. In addition one invited high quality contribution has been included. The papers are organized in the following topical sections: coupling agents and game engines; using games with agents for education; visualization and simulation; and evaluating games with agents.